EMPLOYEE PERFORMANCE IS REVIEWED FROM LEADERSHIP STYLE, MOTIVATION, JOB SATISFACTION AND WORK ENVIRONMENT (Study on Technical Implementation Unit Employees of Central Region Flood Pump Area 1 Semarang City Public Works Office) - Hilamaya, Mahendra Prasanti; Mursito, Bambang; Sarsono, Sarsono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the performance of employees reviewed from leadership style, motivation, job satisfaction, and work environment in the technical implementation unit of the central area flood pump area1 at the Semarang City Public Works Office. The research was conducted using a descriptive quantitative approach. The population in this study is all technical implementers of the flood pump area in the central region 1di Public Works Office of Semarang City. 61. The sample used a census technique of 61 employees because the population is less than 100 people. Methods for data analysis that have been used classical assumption test and multiple linear regression analysis. The study results showed that employee performance is influenced by leadership style, motivation, job satisfaction and work environment. Partially the performance variable significantly affects 5% on leadership style, motivation, job satisfaction and work environment in the technical implementation unit of the central area flood pump area 1 at the Semarang City Public Works Office. Therefore, it is expected that the Semarang Public Works Office can choose the right leadership style and reward employees to increase motivation in achieving work performance and needed improvements to the work environment so that employees feel at home and want to improve the performance of each employee. Employee Performance, Motivation, Job Satisfaction, Work Environment